2019
DOI: 10.1021/acs.bioconjchem.9b00664
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Electrostatic Assembly of a Polymer Surfactant Corona Increases Activity of the Phosphotriesterase arPTE

Abstract: We present a new methodology for the generation of discrete molecularly dispersed enzyme− polymer−surfactant bioconjugates. Significantly, we demonstrate that >3-fold increase in the catalytic efficiency of the diffusion-limited phosphotriesterase arPTE can be achieved through sequential electrostatic addition of cationic and anionic polymer surfactants, respectively. Here, the polymer surfactants assemble on the surface of the enzyme via ion exchange to yield a compact corona. The observed rate enhancement is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 41 publications
(82 reference statements)
1
17
0
Order By: Relevance
“…In addition, modification of the acidic residues on the catalytic cleft may lead to enzymatic deactivation. To mitigate such challenges, Zhang et al prepared SENs via layer-by-layer assembly of oppositely charged surfactants on the protein surface . This appealing strategy improved enzymatic activity; however, stability may be insufficient at elevated ionic strengths when electrostatic interactions are weakened.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, modification of the acidic residues on the catalytic cleft may lead to enzymatic deactivation. To mitigate such challenges, Zhang et al prepared SENs via layer-by-layer assembly of oppositely charged surfactants on the protein surface . This appealing strategy improved enzymatic activity; however, stability may be insufficient at elevated ionic strengths when electrostatic interactions are weakened.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the surfactant corona, there was a reduction in binding site availability for [C‐Av][S], indicating a potential trade‐off between high thermal stability and binding activity. To increase the activity of solvent‐free biofluids, there are possible methodologies emerging from the literature, such as the use of cationic and anionic surfactants instead of cationization with a diamine (Zhang et al, 2019), and the use of site‐directed mutagenesis (Zhou et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The reversibility of the binding pocket was investigated by displacing HABA (λ max = 350 nm) from the Av-HABA complex (λ max = 500 nm) with biotin. The absolute data showed that Av possessed a K d of 1.12 × 10 −5 M (Table S6) as the use of cationic and anionic surfactants instead of cationization with a diamine (Zhang et al, 2019), and the use of site-directed mutagenesis (Zhou et al, 2019).…”
mentioning
confidence: 99%
“…Pérez et al later showed that it was possible to improve on the activity through careful consideration of the cationization process, doubling the activity of the solvent-free lipase as a result. 66 Recently, solvent-free enzyme substrate scope has been expanded with Zhang et al demonstrating phosphotriesterase activity 67 and Mukhopadhayay et al demonstrating protease activity. 68 In addition, Atkins et al…”
Section: Thermal Stability and Anhydrous Activitymentioning
confidence: 99%
“…The first is Please do not adjust margins Please do not adjust margins based on controlling the chemistry of the modification: Deller et al sought to control the kinetics of the cationization process to ensure active site preservation in thrombin 73 , and Zhang et al used a combination of anionic and cationic polymer surfactants to circumvent the requirement of covalent modification entirely. 67 The second approach is realized through utilisation of synthetic biology to modify the protein itself to be more amenable to chemical modification. For example, Zhou et al used site directed mutagenesis to ensure that chemical modification did not alter the active site of lipase, increasing subsequent activity as a result.…”
Section: Prospects and Challengesmentioning
confidence: 99%